Enhancing civil engineering surveying learning through workshops - Awange, Joseph; Anwar, A.; Forootan, E.; Nikraz, Hamid; Khandu, K.; Walker, J. (American Society of Civil Engineers, 2017)
Surveying in an undergraduate civil engineering curriculum needs a substantial amount of hands-on training to obtain adequate learning outcomes. A lecture-only mode of delivery does not provide the adequate surveying skills needed by an engineering student. In 2009, workshops were introduced for the CVEN2000 Civil Engineering Drawing and Surveying unit at Curtin University, Australia, with the aim of offering students hands-on training in surveying to enhance their learning. This study analyzes data collected from 160 students in 2012 and 2013 using confidence limits, correlations, frequency percentage distribution, and principal component analysis to evaluate if the introduced workshops contributed to the enhancement of (1) the students acquiring industry-based skills and (2) the students' overall learning of engineering surveying, which is a practical-oriented course. Additionally, qualitative analysis from Curtin's official eVALUate and examination results were used to verify the findings of the previously mentioned contributions. The results indicate that workshops contributed to the development of the students' overall learning skills, with the top agreement of the students being critical thinking skills (93.6%), handling problems (96.6%), and correlating theory (97.9%). Qualitative analysis of the 2013 data indicates that 70% of the students agreed that their overall learning skills were enhanced and that the workshop sessions prior to the assessed fieldwork of setting out the horizontal curves enhanced their communication and teamwork skills. Overall, 97.9% of the students were satisfied with the workshops, and 98.9% of the students said that they would recommend them as an effective learning tool to their friends. The main lesson learned from the data presented in this paper is that students were satisfied with the workshops and recognized/perceived them to contribute to the development of the learning attributes they need to acquire.